Study on quality of life of chronic kidney disease stage 5 patients on hemodialysis - Gyawali, Mahasagar; Paudel, HC; Chhetri, PK; Shankar, PR; Yadav, SK (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Chronic Kidney Disease (CKD) is a worldwide public health problem with increasing incidence and prevalence. The causes of CKD may be diabetes mellitus, hypertension and polycystic kidney disease. The main objective of this study is to study quality of life of chronic kidney disease stage 5 patients on hemodialysis. Material and Methods: This is a prospective cross sectional study conducted at National Academy of Medical Sciences, B & B Hospital and Blue Cross Hospital, Kathmandu, Nepal on 50 CKD stage 5 patients on hemodialysis. Quality of life among hemodialysis patients was studied using Short Form-36. The result was obtained by comparing the patient’s physical, social and mental status at the beginning and conclusion of a 2 month period. The data was analyzed using the software Statistical Package for Social Sciences (SPSS for Windows version 16). Results: Out of the total 50 patients on hemodialysis, 32 were male (64%) and 18 were female (36%) with mean and median age of patients of 47.14 ± 16.65 and 48.50 years respectively. Out of eight domains studied, energy level, feeling of happiness with life and thought of full energy on self and worning out of life and tiredness perception was found to be equal on pre and post stage. Physical functioning was found to be decreased. Patients on hemodialysis reported improvements in nearly all aspects of general functioning and psychological well-being. Conclusion: This result demonstrates that there were several changes in Quality of life. Hemodylasis improves the Quality of life however, there was significant decrease in physical functioning, role limitation due to physical ill health, role limitation due to decreased emotional wellbeing, and reduced general health. Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (2): 26-31 DOI: http://dx.doi.org/10.3126/jmcjms.v1i2.9265